APLIKASI JOIN OPERATION ANTARA KSU DENGAN LKM DALAM PENGADAAN ALAT-ALAT BERAT MENURUT HUKUM EKONOMI SYARIAH - Aljuhani, Kholid; Aminulloh, Ali; Rojak Samsudin, Agus (Cahaya Ilmu Bangsa, 2024)
Join operation is a cooperation between two or more business entities to complete a temporary project. Syirkah is one of the cooperation between two or more people in a business where both are responsible for profits and losses and are based on mutual assistance. Join Operation between KSU and LKM in the Procurement of Heavy Equipment can be considered as cooperation between institutions. The purpose of this study is to determine the practice of joint operations between KSU and LKM in the procurement of heavy equipment and the practice of joint operations between KSU and LKM in the procurement of heavy equipment according to sharia economic law. The method used in this research is a qualitative approach with the type of field research. Data collection techniques in the form of observation, interviews with the secretary, treasurer, KSU financial administration staff with LKM and supplemented with documentation. The results showed, first, that the practice of joint operations between KSU and LKM begins with the LKM surveying the prices and specs of heavy equipment needed in building a project to the manufacturer, after the survey the two parties meet to deliberate and negotiate so that there is a mutual agreement, this is an MOU agreement between KSU and LKM in the procurement of heavy equipment and there are contributions from each party. After the MOU, KSU releases funds in cash to be given to LKM, then LKM buy heavy equipment and provide benefits to KSU in installments. Second, the practice of joint operation between KSU and LKM in the procurement of heavy equipment according to sharia economic law in its implementation has fulfilled the pillars, conditions and principles of syirkah according to Islamic teachings. So, both parties do not appear to have elements that are prohibited by Islamic law in cooperating (syirkah) but in practice there are similarities with murabahah in terms of financing and musyarakah mutanaqisah in terms of operations. This is because both parties in the cooperation are mutually consensual, mutual help and mutual openness, because both parties want to help each other in the procurement of this heavy equipment. Keywords: Join Operation, Syirkah, Heavy Equipment;